2015
DOI: 10.1590/1983-1447.2015.01.47694
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bariatric surgery results

Abstract: The objective was to evaluate the results of bariatric surgery in patients in the late postoperative period using the Bariatric Analysis and Reporting Outcome System (BAROS). This cross-sectional study was conducted from November 2011 to June 2012 at a hospital in the state of Ceará, Brazil. Data were collected from 92 patients using the BAROS protocol, which analyzes weight loss, improved comorbidities, complications, reoperations and Quality of Life (QoL). Data were analysed using the chi-squared test, Fisch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 14 publications
6
14
0
10
Order By: Relevance
“…The most common comorbidities were hypertension (42.4%), sleep apnea (24.1%) and diabetes (18.2%). These data were also found in other studies 17,18,20,23 . Barros et al 23 found an even higher prevalence of hypertension (50%) in the preoperative period.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The most common comorbidities were hypertension (42.4%), sleep apnea (24.1%) and diabetes (18.2%). These data were also found in other studies 17,18,20,23 . Barros et al 23 found an even higher prevalence of hypertension (50%) in the preoperative period.…”
Section: Discussionsupporting
confidence: 90%
“…When analyzing the relationship between bariatric surgery and its impact on weight loss, we noted, as others did, that this procedure has been shown to be quite effective 12,20,21,23 . The mean BMI before and after surgery was 48.10kg/ m 2 and 31.05kg/m 2 , respectively, which implies a significant reduction in cardiovascular mortality and in mortality from all causes associated with excessive weight 7,18 .…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations